Deposition of annual growth lines in the apex of the common limpet (Patella vulgata) from Shetland Islands, UK and Norway: Evidence from field marking and shell mineral content of annual line deposition. (2nd January 2016) - Ambrose, William G.; Locke V, William L.; Bigelow, Gerald F.; Renaud, Paul E.
Abstract : The abundance, accessibility and value of limpets as a source of food and bait for coastal peoples have resulted in their high frequency in shell middens worldwide. The limpet Patella vulgata is found in middens from the Mediterranean to Norway, and morphometric and sclerochronological analyses of its shell can provide insight into harvesting patterns and paleoenvironmental variables valuable in reconstructing climate. Previous work with P. vulgata has relied on lines on the exterior of the shell, or on lines exiting on the shell surface in shell cross-section, as annual or sub-annual markers. Shell damage may compromise these lines and limit the use of some shells, but growth lines are also found in the better-preserved shell apex. We investigated whether the growth lines in the apex of P. vulgata from two locations in Northern Europe are annual using calcein-marking and recapture. Investigations were performed at one site in the Shetland Islands (UK) and at one site at the northern limit of P. vulgata 's range in Northern Norway. We also used laser ablation to measure the concentration of minerals in the shells of two individuals from Shetland to determine if patterns of minerals suggested as bioproxies for temperature and productivity varied annually. All individuals deposited one growth line in the apex during their year in the field, and the lowest ratios of Sr/Ca and Ba/Ca and to a lesser extent Mg/Ca were coincident with annual lines on the shells from Shetland. Growth at both sites was modelled using the von Bertalanffy growth function, and apex growth was nearly five times faster in Shetland than in Norway, probably a result of differences in temperature between the two locations.